Design, Simulation, and Real-Time Implementation of a DC Microgrid Powered by Renewable Hybrid Energy Sources (London Journal of Engineering Research, 2025)
When large amounts of renewable energy sources are integrated, DC microgrids face difficulties with voltage regulation, energy management, inertia control, and uncertainty management. Numerous approaches have been offered to address these difficulties, such as droop control, centralized control, distributed control, virtual inertia control, and uncertainty management algorithms. Despite these efforts, a comprehensive overview that offers a panoramic understanding of the existing techniques and forthcoming trends in controlling renewable energy-integrated DC microgrids has been lacking. This paper involves designing, simulating, and implementing a DC Microgrid based on hybrid renewable energy sources to achieve high efficiency and sustainability in energy systems. The research focuses on integrating solar and wind energy sources with the design of an advanced energy management system that ensures network stability and reduces electrical losses. A comprehensive mathematical model was developed to study network dynamics and analyze its response to operating conditions, such as climate and load changes. High-precision numerical simulation techniques were adopted to analyze the performance and improve the compatibility between the network components to achieve maximum operational efficiency. The research includes designing and implementing a controller to manage the real-time dynamic balance between energy generation and consumption. Practical tests of the proposed system were conducted in realistic operating environments to study the network's performance in multiple cases, such as peak loads and sudden outages.
Keywords: Fuzzy controller; PID controller; two-wheeled balance robot